Relationships between muscle quality, subcutaneous adipose tissue, and sprint performance markers of competitive cyclists - Cesanelli, L.; Kamandulis, S.; Volungevicius, G.; Satkuskiene, D. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Many variables are considered to be determinants of cycling sprint performance. Among them, the importance of skeletal muscle properties in relation to cycling performance has been consistently underlined. The aim of the present study was to evaluate the vastus lateralis (VL), rectus femoris (RF) and vastus medialis (VM), echo intensity (EI) and subcutaneous adipose tissue (SAT) content in a group of competitive cyclists and to identify whether these are related to sprint performance. METHODS: Muscle echo intensity was evaluated by ultrasound in 16 highly trained competitive cyclists. The cyclists performed a maximal-intensity sprint session comprising four 15 s maximal sprints on a Wingate bike with 2 min of recovery between each. Pearson correlational analysis with linear regression was used to identify significant relationships between the criteria EI and SAT content and the sprint performance variables. RESULTS: Muscle EI correlated strongly with sprint performance markers (r=from 0.54 to 0.62; P<0.05), while SAT content and body fat percentage correlated trivially to moderately with sprint performance (r=from 0.07 to 0.40; P>0.05). CONCLUSIONS: Overall, muscle quality of knee extensors was positively related to sprint performance markers, but SAT content was not. Although additional studies are needed, muscle quality may represent a valid body composition indicator and may be helpful for supporting sprint performance optimization procedures in competitive cyclists.